Geografia per l'inclusione Partecipazione attiva contro le disuguaglianze - Pavia, Davide (Tratti geografici. Materiali di ricerca e risorse educative, 2017)
"This volume gathers the contributions related to the call for papers presented on the occasion of the 59th National Conference of AIIG (Faculty of Literature and Philosophy, Sapienza University of Rome, 29 September - 3 October 2016). It aims to provide a lively and faceted testimony of the inclusive values that geography is able to offer to all operators of education and territory. The theoretical contributions of the first part highlight the irreplaceable role of geography to educate to the realization of a really inclusive human community and also touch other issues with a strong social impact, such as the right to health. In the second part the inclusive theories are translated into teaching practice, so that teachers can get practical and effective ideas for the realization of similar projects in other schools and universities."